Development of a malaria knowledge test for student travelers - Laurie B. Hartjes; Linda C. Baumann (MDPI AG, 2012)
This paper describes a malaria knowledge test (MKT) developed to evaluate a web-based game for students who increasingly travel to malariarisk regions of the world. The 18-item MKT was structured according to the dimensions of the self-regulation model (SRM) to measure the accuracy of students’ beliefs about malaria. An experimental design was used to compare three game versions. Students (N=482) participated in 2010 by completing a pre-test, playing a Webbased game simulating student travel to malaria- endemic destinations, and completing a posttest. Study data support the validity and reliability of the MKT for the evaluation of malaria education interventions and for student self-assessment. Use of the MKT to evaluate an educational game about malaria revealed a strong overall learning effect and discrimination by game version, travel experience, and SRM dimension. This 5-min test may also be adapted for educational outreach purposes among health care providers globally, residents of malaria-endemic regions, and other high risk travel groups (e.g., elderly, chronic health conditions, pregnant, or returning to malaria-endemic regions to visit friends/relatives).